Application of hotelling’s T² control chart for a machining process of the inside diameter of a steel cylinder - Henning, Elisa; Maia, Murilo Thiago da; Walter, Olga Maria Formigoni Carvalho; Konrath, Andrea Cristina; Alves, Custodio da Cunha (Revista Gestão da Produção Operações e Sistemas, 2014)
The quality of products and processes has proven to be crucial for companies to compete in the market. Statistical process control enables them to foresee problems in the process, thereby ensuring the quality of manufactured items. This paper aims to present a proposal for monitoring a machining process, with the help of this tool using control charts. This research arose from the need to monitor the rectification process of the inside diameter of a steel cylinder, a component of a product manufactured in a company in southern Brazil. The parameters must follow design specifications, so the final product will not have performance problems. Thus, for monitoring this process, Shewhart X -S control charts are used for three measurements performed in sections of a cylinder, analyzing them separately. To complement, a multivariate Hotelling’s T2 chart is used to monitor these three measurements simultaneously. The two approaches are compared in terms of performance and usage aspects. The results obtained in terms of performance were similar. However, the Shewhart control chart is easier to use and simpler to interpret by operators. The results enabled the company to know process stability, facilitating decision-making on actions taken for improvement.